2016
DOI: 10.1093/heapro/daw052
|View full text |Cite
|
Sign up to set email alerts
|

Promoting health by addressing living conditions in Norwegian municipalities

Abstract: Worldwide, inequalities in health are increasing, even in well-developed welfare states such as Norway, which in 2012, saw a new public health act take effect that enshrined equity in health as national policy and devolved to municipalities' responsibility to act on the social determinants of health. The act deems governance structures and "Health in All Policies" approaches as important steering mechanisms for local health promotion. The aim of this study is to investigate whether Norway's municipalities addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…It also still remains to be seen whether the transferring of more responsibility to the municipalities in The Public Health Act will strengthen or weaken efforts to reduce social inequalities in health. Most of the municipalities (82 per cent) believe they are capable of reducing inequalities in health, and the larger municipalities more often than smaller ones see living conditions as a main challenge in health promotion (Hagen et al, 2016).…”
Section: Concluding Discussion: What Future For the Norwegian Health mentioning
confidence: 99%
“…It also still remains to be seen whether the transferring of more responsibility to the municipalities in The Public Health Act will strengthen or weaken efforts to reduce social inequalities in health. Most of the municipalities (82 per cent) believe they are capable of reducing inequalities in health, and the larger municipalities more often than smaller ones see living conditions as a main challenge in health promotion (Hagen et al, 2016).…”
Section: Concluding Discussion: What Future For the Norwegian Health mentioning
confidence: 99%
“…Other research has shown that the municipalities have struggled to integrate health promotion in their planning processes. In a survey conducted in 2014, only 25% of the municipalities reported that they had conducted the overview of the health situation in their municipality that would serve as the data basis for the plan [24].…”
Section: Discussionmentioning
confidence: 99%
“…The surveys showed that the municipalities to a small extent had adopted the principles of HiAP and HI [23,24]. Many municipalities focused mainly on lifestyle-and health care-related measures.…”
Section: Hiap and Social Equity-the "New" Concept Of Public Healthmentioning
confidence: 99%
“…Partisan trends are however not present in our data. Acknowledging living conditions as a public health priority is independent of political profile, first and foremost in the larger cities [10,21], leading us to believe that municipalities put policies to create health equity on the agenda when challenges are (27) 44 (19) manifest. Nevertheless, the laws are important institutional and organisational frameworks that set the rules by regulating policies, as well as public health activities in municipalities.…”
Section: Leadership and Governancementioning
confidence: 99%
“…Institutions regulate the relation between the state and individuals, and because the decentralisation of service provision is an important feature of the Norwegian welfare state, municipalities are the institutions that provide services and communicate with citizens. This encompasses their two roles: their frontline responsibility to implement national policy goals and their role as democratic decision-making bodies [10].…”
mentioning
confidence: 99%